Association Between Atrial Fibrillation and the Risk of Cardiovascular Mortality Among Elderly Adults With Ischemic Stroke in Northeast China: A Community-Based Prospective Study - Xia, Zhenwei; Dang, Wei; Jiang, Yang; Liu, Shuang; Yue, Ling; Jia, Fengshuo; Sun, Qun; Shi, Lei; Sun, Jixu; Li, Jiao; Chen, Hongyun (Frontiers in Aging Neuroscience, 2022)
Background Elderly people are susceptible to atrial fibrillation (AF) and ischemic stroke (IS), however, little is known about the association between AF and the risk of cardiovascular disease (CVD) mortality in the elderly population with IS. We aimed to investigate the features of AF among aged people with IS, and to illustrate whether AF accounted for CVD mortality. Methods At baseline, 790 patients with IS were enrolled from general northeast Chinese elderly population (>60 years) between September 2017 to March 2019. The prevalence, awareness and treatment of AF in each age group were analyzed, as well as major related cardiovascular risk factors. The population was followed until July 31, 2021, information on CVD death was obtained. Results Twenty-five people had AF and the prevalence of AF in elderly IS population was 3.2%. The AF prevalence grew along with age from 1% (60-64 years) to 4.3% (70-74 years) and 4.2% (≥ 75 years), which was higher in urban than in rural residents (5.7% vs 2.2%, P=0.014). The awareness and treatment rates of AF patients were 80% and 8%. After a median follow-up of 3.3 years, 58 subjects died due to CVD, and 5 were accompanied with AF (rate 70.6/1,000 person-years). Elderly ischemic stroke patients with AF had a 3.65-fold increased risk of CVD death in the fully adjusted model when compared to non-AF participants. Conclusion AF prevalence increased with age among elderly IS population. Moreover, elderly IS patients in northeast China with AF had a higher CVD mortality. Therefore, early screening, and prompt management of AF in elderly IS population in northeast China are required.